Algebraische Zahlentheorie: 22.8. bis 28.8.1971 - Hasse, Helmut; Roquette, Peter (Tagungsbericht, 1971)
Y. Amice, Paris; C. Arf, Ankara; J. V. Armitage, Nottingham; H. Benz, Köln; L. Bernstein, Chicago; B. J. Birch, Oxford; E. Brettler, Bonn; P. Brignon, Mulhouse; C. J. Bushnell, London; R. W. D. Davis, San Diego; P. K. J. Draxl, Bielefeld; G. Frei-Imfeld, Zürich; A. Fröhlich, London; Haifawi, Ankara; U. Halbritter, Köln; H. Hasse, Hamburg; M. Hazewinkel, Rotterdam; H. Jacobinski, Göteborg; W. Jehne, Köln; N. Klingen, Köln; K. Lakkis, Thessaloniki; E. Lamprecht, Saarbrücken; D. H. Lehmer, Berkeley; E. Lehmer, Berkeley; J. B. Leicht, Heidelberg; A. Leutbecher, München; H. v. Lienen, Bochum; J. Martinet, Bordeaux; H. Mathieu, Saarbrücken; R. Mauve, Köln; L. R. McCulloh, London; C. Meyer, Köln; J. Neukirch, Regensburg; J. Ochoa, Madrid; J.-J. Payan, Grenoble; D. Pawliska, Köln; M. Peters, Münster; M. Pohst, Köln; G. Poitou, Orsay; H. Popp, Lafayette; P. Roquette, Heidelberg; W. Scharlau, Münster; R. Schertz, Köln; V. Schulze, Clausthal-Zellerfeld; H. K. Schmidt, Würzburg; N. M. Stephens, Chilton; A. Volkenborn, Köln; R. W. v. d. Waall, Nijmegen; H. H. Wicke, London; S. M. J. Wilson, London; H. G. Zimmer, Karlsruhe
Beitr. teilw. dt., teilw. engl
Keywords: Konferenzschrift